Internal Stipe Necrosis of Agaricus bisporus - Etiology and Molecular Genetic Studies - Inglis, Peter Ward (1996)
The button mushroom, Agaricus bisporus is the most popular mushroom in cultivation worldwide, and is the most valuable protected crop in the UK, with an estimated wholesale value exceeding £250 million. In 1991 a new disease emerged in mushroom crops in the UK, called Internal Stipe Necrosis (ISN). Crop losses due to this disease may reach 10 %, since affected mushrooms must be downgraded or discarded. Symptoms take the form of a variable browning reaction in the central region of the mushroom stipe, which may also demonstrate varying degrees of internal collapse.